Camarões (Atyidae e Palaemonidae) da rede fluvial do Estado do Rio de Janeiro: sistemática e distribuição - Fonseca, Kátia Maria Leal da (1995)
Systematics and geographic distribution of freshwater shrimps (Atyidae and Palaemonidae) from the Rio de Janeiro fluvial system were studied. Some environmental factors (salinity, temperature, declivity and oxygen) influence upon species distribution. This dissertation contains an introduction, systematic part, discussion, conclusions, bibliography, three squares, five maps and ten plates corresponding to the species studied. Keys for classification of families and species, diagnosis of families and subfamilies are shown. Characterization, size, type locality, geographic distribution, material examined and notes for each species are mentioned. The occurrence of one species not yet recorded from the region is mentioned, the validity of one species is discussed, and reported factors which influence upon the species distribution. The species are distributed according to the hydrographic basins delimitated for SERLA (Superintendência Estadual de Rios e Lagos) in 1985.